PERBANDINGAN BIAYA DAN WAKTU PEKERJAAN DINDING PASANGAN BATA MERAH DAN BATU KUMBUNG PERUMAHAN GRIYA PERMATA INSANI - Mashudin Mashudin; Rasio Hepiyanto (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2017)
Contruction expanded rapidly and spread in Lamongan, from fairly simple residential contractor to large developer continuing to explore in building construction. This research aims to know the comparative costs of wall job using material white brick and red brick based on analysis of a contractor with the methodof 2017 SNI job and time of wall job white brick  and red brick per m2 using method Daily Record Sheet that is by direct observation and recording work time couples wall field. The result of the research conducted is found the cost of work required for couples wallwhite stone per m2 using analysis of contractor is Rp. 66.020,-/m2 and a pairof red brick wall is Rp. 75.020,-/m2. The cost of the work required for the pair of wall stone kumbung per m2 based on SNI method 2017 is Rp. 109.910,-/m2 and pair of red brick wall is Rp. 113.100,-/m2. After the comparison then it can be inferred that the couple wall using white brick cheaper than the pair of red brick wall, but the difference is not too significant is Rp 9,000,-per m2 with contractor method and IDR 3,190,-per m2using SNI 2017method. The time it takes to complete the job of couple wall using red brick per m2 is 0.445 hours/m2, whereas the time required on the job of couple wall using white brick is 0.324 hours/m2. So the job of  the couple wall using white brick more efficient 0.121 hours/m2 compared with red brick wall.